2017
DOI: 10.2519/jospt.2017.7227
|View full text |Cite
|
Sign up to set email alerts
|

Young Athletes Cleared for Sports Participation After Anterior Cruciate Ligament Reconstruction: How Many Actually Meet Recommended Return-to-Sport Criterion Cutoffs?

Abstract: Rupture of the anterior cruciate ligament (ACL) is a devastating injury that occurs with high frequency among individuals who participate in cutting and pivoting sports. 24,48 Anterior cruciate ligament reconstruction is commonly performed with the goal of facilitating return to sports activities. However, recent metaanalysis data from over 7000 participants following ACL reconstruction demonstrated that 65% returned to their previous level of sport and only 55% returned to competitive sports.3 Factors associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
167
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(178 citation statements)
references
References 58 publications
(85 reference statements)
6
167
4
1
Order By: Relevance
“…This lack of follow-up is particularly concerning considering high rates of second ACL injury in younger, more active patients,10 and because only a minority of patients successfully fulfil return to sport battery testing when attempting to return to sport earlier than 1 year 11. Furthermore, continued follow-up may be necessary to fulfil objective strength tests associated with a return to same level of sports participation 12. Considering low rates of return to the same competitive level sport after ACLR (55%),13 it may be important for orthopaedic surgeons and/or physical therapists to continue follow-up past sport clearance, in order to assess deficiencies and optimise postsurgical rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of follow-up is particularly concerning considering high rates of second ACL injury in younger, more active patients,10 and because only a minority of patients successfully fulfil return to sport battery testing when attempting to return to sport earlier than 1 year 11. Furthermore, continued follow-up may be necessary to fulfil objective strength tests associated with a return to same level of sports participation 12. Considering low rates of return to the same competitive level sport after ACLR (55%),13 it may be important for orthopaedic surgeons and/or physical therapists to continue follow-up past sport clearance, in order to assess deficiencies and optimise postsurgical rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-report criteria were used in 26 (12%) of the 209 studies and included the subcategories patient-reported outcome measures (PROMs), subjective statements and reports of pain (table 7). Six studies [37][38][39][40][41][42] (3%) used one outcome measure, and two studies 43 44 (1%) used two measures. One study 45 reported pain and subjective reports as RTS criteria and one study 40 used PROMs and subjective statements as RTS criteria.…”
Section: Patient-report (Contextual Factors)mentioning
confidence: 99%
“…35 Among young active ACLR individuals, less than half may fulfill a ≥90% LSI criterion for quadriceps strength. 7,36,37 Within ACLinjured adults, Welling et al 38 reported that only 13 patients out of 62 (21%) reached ≥90% LSI criterion for quadriceps strength 9 months after ACLR. In a study by Cristiani et al 8 where 4093 patients were assessed 6 months after ACLR, 36% and 47% reached the ≥90% LSI criterion for quadriceps and hamstring strength, respectively.…”
Section: Introductionmentioning
confidence: 99%